Biogas production from chicken manure: Co-digestion with spent poppy straw - ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2017)
Co-digestion of chicken manure (laying hens) and spent poppy straw was investigated in a daily fed laboratory scale mesophilic anaerobic digester. The digester was operated for 240 days and the methane yield was monitored by increasing the organic loading rate (OLR) from 2.78 to 3.56 g VS l(-1)d(-1) and the total ammonia nitrogen (TAN) up to 6650 mg l(-1). The highest methane yield of 0.36 I g VS-1 was obtained when the TAN and free ammonia nitrogen (FAN) concentrations were below 4000 and 300 mg l(-1), respectively. The results showed that microbial consortia were acclimated to high ammonia concentrations and a methane yield of about 0.28 I g VS-1 was achieved up to 6100 mg l(-1)of TAN. When the TAN concentration in the digester increased above 6500 mg 1'1, the methane yield sharply decreased below 0.14 I g VS-1. (C) 2016 Elsevier Ltd. AU rights reserved.
Keywords: Acclimation; Ammonia inhibition; Laying hens; Methane; SYNTROPHIC ACETATE OXIDATION; SOLID ANAEROBIC-DIGESTION; AMMONIA INHIBITION; METHANE PRODUCTION; FERMENTATION; COMMUNITY; STOVER